2018
DOI: 10.1007/s11548-017-1701-7
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific estimation of detailed cochlear shape from clinical CT images

Abstract: The paper presents the process of building and using the SDM of the cochlea. Compared to current best practice, we demonstrate competitive performance and some useful properties of our method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…There are also likely differences in the way the gold-standard and clinical coordinate systems were aligned. Kjer et al 23 reported mean surface errors of 0.11 mm for the cochlear scalae.…”
Section: Experiments Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…There are also likely differences in the way the gold-standard and clinical coordinate systems were aligned. Kjer et al 23 reported mean surface errors of 0.11 mm for the cochlear scalae.…”
Section: Experiments Results and Discussionmentioning
confidence: 98%
“…Evaluation metrics were based on Dice similarity coefficients and surface errors, so it is unclear how well this method can estimate surgically relevant parameters. Kjer et al 23 developed a similar approach using a statistical deformation model, reporting measurement accuracy and precision for cochlear length, width and height in addition to surface errors, but with no consideration of vertical trajectories. van der Jagt et al 24 describe an automatic, three-dimensional tracing method that was used to estimate inner and outer wall radii, duct diameter and vertical trajectory in low-resolution CT scans of 242 patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These algorithms can then be used to build anatomical models from clinical CT imaging, allowing accurate 3D reconstruction of a patient’s anatomy. Creation of automatic segmentation algorithms requires tedious manual segmentation of micro-CT data, therefore many groups have been working on automating segmentation with polynomial functions [10], atlas-based registration [11], SSMs [1214], and deep learning [15, 16]. Further, labour intensive manual segmentation often leads to smaller sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Segmentation of these structures in 3D is important for surgical planning [3], robotic surgery [4], virtual-reality surgical simulation [57], and patient-specific cochlear implant programming [8, 9]. Unfortunately, manual segmentation is very labour intensive, therefore many groups have been working on automating segmentation with polynomial functions [10], atlas-based registration [11], statistical shape models [1214], and deep learning [15, 16]. This type of research requires large datasets, and many groups have made their datasets publicly available to help the larger research community [17].…”
Section: Introductionmentioning
confidence: 99%